2018
DOI: 10.1128/jcm.00940-18
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Quantifying Lyme Pathogen Strains by Deep Sequencing of the Outer Surface Protein C (ospC) Locus

Abstract: A mixed infection of a single tick or host by Lyme disease spirochetes is common and a unique challenge for the diagnosis, treatment, and surveillance of Lyme disease. Here, we describe a novel protocol for differentiating Lyme strains on the basis of deep sequencing of the hypervariable outer surface protein C locus (). Improving upon the traditional DNA-DNA hybridization method, the next-generation sequencing-based protocol is high throughput, quantitative, and able to detect new pathogen strains. We applied… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Studies on wild I. ricinus nymphs found that 77-79% of the nymphs are co-infected with multiple strains of B. afzelii and that nymphs carry an average of 2.4-2.9 strains (Durand et al, 2015(Durand et al, , 2017. Numerous studies in North America have found that wild I. scapularis ticks are commonly infected with multiple strains of B. burgdorferi ss (Wang et al, 1999;Qiu et al, 2002;Brisson and Dykhuizen, 2004;Walter et al, 2016;Di et al, 2018). Thus, co-infected nymphs are the norm rather than the exception in areas where Lyme disease is endemic.…”
Section: Relevance Of Our Study To the Situation In Naturementioning
confidence: 99%
“…Studies on wild I. ricinus nymphs found that 77-79% of the nymphs are co-infected with multiple strains of B. afzelii and that nymphs carry an average of 2.4-2.9 strains (Durand et al, 2015(Durand et al, , 2017. Numerous studies in North America have found that wild I. scapularis ticks are commonly infected with multiple strains of B. burgdorferi ss (Wang et al, 1999;Qiu et al, 2002;Brisson and Dykhuizen, 2004;Walter et al, 2016;Di et al, 2018). Thus, co-infected nymphs are the norm rather than the exception in areas where Lyme disease is endemic.…”
Section: Relevance Of Our Study To the Situation In Naturementioning
confidence: 99%
“…Diverse genomic groups co-exist within LB populations, often infecting a single tick and presumably a single vertebrate host (Rauter and Hartung, 2005;Andersson et al, 2013;Di et al, 2018). Multilocus linkage disequilibrium (nonrandom distribution of genetic alleles) among LB strains was first noted at three genetic loci (p93, fla, and ospA) based on a number of isolates which are now recognized as distinct LB species (Dykhuizen et al, 1993).…”
Section: Lb Populations Contain Well Defined Genomic Groupsmentioning
confidence: 99%
“…Second, genomic groups within B. burgdorferi vary in disease propensities. At least 18 B. burgdorferi genomic groups, corresponding to major sequence variations at ospC (allelic types A-O, T, and U) cosegregate with chromosome-based phylogeny in northeast USA populations (Wang et al, 1999c;Barbour and Travinsky, 2010;Di et al, 2018). Initially, four groups (ospC types A, B, I, and K) were found to be strongly associated with disseminated (i.e.…”
Section: Lb Populations Contain Well Defined Genomic Groupsmentioning
confidence: 99%
“…Considerable OspC diversity has been demonstrated among LD spirochete strains isolated from tightly defined geographic regions (Wang et al, 1999;Lin et al, 2002;Alghaferi et al, 2005;Earnhart et al, 2005). Twenty-one OspC types have been demonstrated in a single tick through deep sequencing (Di et al, 2018). B. burgdorferi isolates recovered from naturally infected animals (Seinost et al, 1999b;Oliver Jr et al, 2016; or from the tissues of dogs experimentally infected with field collected ticks (Rhodes et al, 2013) are highly heterogenous with regard to the OspC types represented.…”
Section: Ospc Phylogenymentioning
confidence: 99%